Surface deformation of moving droplets of slurry fuels; Physics of Fluids; Vol. 36, iss. 5 - Kuznetsov G. V. Geny Vladimirovich; Strizhak P. A. Pavel Alexandrovich; Volkov R. S. Roman Sergeevich; Vysokomornaya O. V. Olga Valeryevna (2024, 2024)
Title screen